Paternal predictors of the mental health of children of Vietnamese refugees - Rousseau Cécile; Thomsen Per H; Vaage Aina B; Wentzel-Larsen Tore; Ta Thong V; Hauff Edvard (BMC, 2011)
Abstract Background Intergenerational transmission of trauma as a determinant of mental health has been studied in the offspring of Holocaust survivors and combat veterans, and in refugee families. Mainly negative effects on the children are reported, while a few studies also describe resilience and a possible positive transformation process. A longitudinal prospective cohort study of Vietnamese refugees arriving in Norway in 1982 reports a 23 years follow-up, including spouses and children born in Norway, to study the long-term effects of trauma, flight, and exile on the offspring of the refugees. Objectives of the study: 1. To study the association between the psychological distress of Vietnamese refugee parents and their children after 23 years resettlement. 2. To analyse paternal predictors for their children's mental health. Methods Information from one or both parents at arrival in 1982 (T1), at follow-up in 1985 (T2), and 23 years after arrival (T3) was included. The mental health was assessed by the Global Severity Index (GSI) of the self-report Symptom Check List-90-R (SCL-90-R) for parents (n = 88) and older children (age 19-23 yrs, n = 12), while children aged 4-18 (n = 94) were assessed using the Strengths and Difficulties Questionnaire (SDQ). Results Thirty percent of the families had one parent with a high psychological distress score ("probable caseness" for a mental disorder), while only 4% of the children aged 10 - 23 years were considered as probable cases. In spite of this, there was an association between probable caseness in children and in fathers at T3. A significant negative paternal predictor for the children's mental health at T3 was the father's PTSD at arrival in Norway, while a positive predictor was the father's participation in a Norwegian network three years after arrival. Conclusions Children of refugees cannot be globally considered at risk for mental health problems. However, the preceding PTSD in their fathers may constitute a specific risk for them.